(untitled) (The Review of Diabetic Studies, 2025)
Background: Airports and seaports serve as critical points of entry (PoE) for global travel and trade, representing both opportunities and vulnerabilities for public health. Saudi Arabia, hosting millions of international travelers annually for Hajj and Umrah, faces unique challenges in preventing and managing communicable diseases at these PoE. Objectives: This systematic review aimed to synthesize empirical evidence on health security at points of entry in Saudi Arabia, focusing on airports and seaports, to identify strengths, gaps, and recommendations for policy and practice. Methods: Following PRISMA 2020 guidelines, peer-reviewed articles and grey literature published between 2009 and 2025 were systematically reviewed. Eligible studies included quantitative, qualitative, and mixed-methods research addressing surveillance, preparedness, traveler knowledge, and emergency response systems at PoE in Saudi Arabia and comparable regions. Results: Twenty-four studies met the inclusion criteria. Findings indicated variable levels of traveler knowledge and preventive practices, with only 28.2% of travelers in Jeddah demonstrating good knowledge of travel health. Pre-travel consultation uptake was low, with 76.8% never seeking advice. Surveillance systems during Hajj improved outbreak detection but revealed gaps in coordination and logistics. Malaria cases reemerged in Jeddah (n=2,124, 2018–2023), highlighting the risk of disease importation. COVID-19 screening programs detected 13.5% positive cases in mass screening, and pandemic disruptions altered influenza subtype patterns. Additional risks were noted in food and water safety at airports, as well as limited preparedness for non-communicable emergency cases. Conclusion: Saudi Arabia has made significant progress in developing surveillance and response systems at points of entry, yet gaps in traveler awareness, emergency preparedness, and coordination persist. Addressing these challenges through integrated health education, stronger logistics, culturally sensitive communication, and alignment with international frameworks such as IHR 2005 is essential to enhance national and global health security.